Cytogenetic analyses of eight species in the genus Leptodactylus Fitzinger, 1843 (Amphibia, Anura, Leptodactylidae), including a new diploid number and a karyotype with multiple translocations - Gazoni, Thiago [UNESP]; Gruber, Simone L. [UNESP]; Silva, Ana P. Z.; Araujo, Olivia G. S. [UNESP]; Narimatsu, Hideki [UNESP]; Struessmann, Christine; Haddad, Celio Fernando Baptista [UNESP]; Kasahara, Sanae [UNESP] (Biomed Central Ltd., 2012)
Background: The karyotypes of Leptodactylus species usually consist of 22 bi-armed chromosomes, but morphological variations in some chromosomes and even differences in the 2n have been reported. To better understand the mechanisms responsible for these differences, eight species were analysed using classical and molecular cytogenetic techniques, including replication banding with BrdU incorporation.Results: Distinct chromosome numbers were found: 2n = 22 in Leptodactylus chaquensis, L. labyrinthicus, L. pentadactylus, L. petersii, L. podicipinus, and L. rhodomystax; 2n = 20 in Leptodactylus sp. (aff. podicipinus); and 2n = 24 in L. marmoratus. Among the species with 2n = 22, only three had the same basic karyotype. Leptodactylus pentadactylus presented multiple translocations, L. petersii displayed chromosome morphological discrepancy, and L. podicipinus had four pairs of telocentric chromosomes. Replication banding was crucial for characterising this variability and for explaining the reduced 2n in Leptodactylus sp. (aff. podicipinus). Leptodactylus marmoratus had few chromosomes with a similar banding patterns to the 2n = 22 karyotypes. The majority of the species presented a single NOR-bearing pair, which was confirmed using Ag-impregnation and FISH with an rDNA probe. In general, the NOR-bearing chromosomes corresponded to chromosome 8, but NORs were found on chromosome 3 or 4 in some species. Leptodactylus marmoratus had NORs on chromosome pairs 6 and 8. The data from C-banding, fluorochrome staining, and FISH using the telomeric probe helped in characterising the repetitive sequences. Even though hybridisation did occur on the chromosome ends, telomere-like repetitive sequences outside of the telomere region were identified. Metaphase I cells from L. pentadactylus confirmed its complex karyotype constitution because 12 chromosomes appeared as ring-shaped chain in addition to five bivalents.Conclusions: Species of Leptodactylus exhibited both major and minor karyotypic differences which were identified by classical and molecular cytogenetic techniques. Replication banding, which is a unique procedure that has been used to obtain longitudinal multiple band patterns in amphibian chromosomes, allowed us to outline the general mechanisms responsible for these karyotype differences. The findings also suggested that L. marmoratus, which was formerly included in the genus Adenomera, may have undergone great chromosomal repatterning.
Keywords: FISH; Replication banding; BrdU; Fluorochrome staining; Ag-NOR; C-banding